Remote education during a pandemic: analysis of emotional and academic factors in university students - Escandón-Nagel, Neli (2024)
The main objective of the research was to analyze remote education in a pandemic experienced by Spanish-speaking university students from 9 countries, through the application of a Remote Learning Questionnaire in Higher Education. Factorial analysis of the instrument, applied to 1136 Spanish-speaking university students, identified five dimensions: Satisfaction with didactic and ethical principles, Self-perception in learning, Diversity and collaboration in assessment, Material conditions, Teachers’ interest in student well-being. All factors correlated positively with student participation. Perception of plagiarism and copying is lower with higher satisfaction with didactic and ethical principles of education and high self-perception of learning. High presence of positive emotions enhances the perception of the educational process, participation, and academic integrity. Findings invite a rethinking of post-pandemic education.